Finite element analysis on the residual bearing capacity of axially preloaded tubular T-joints subjected to impacts. (June 2021) - Deng, Peng; Chen, Xiulong; Yang, Boyi; Guo, Jianxun; Liu, Yan
Highlights: Nonlinear FEA to understand dynamic behavior of square hollow section T-joint. Residual bearing capacity evaluated for SHS T-joints damaged by impact. Effects of axial preloading, impact energy, and geometric parameters considered. Results can be used to guide application and repair of steel tubular structures. Abstract: Understanding the dynamic behavior of tubular members is necessary for ensuring their safety, even when damaged after an impact. A nonlinear finite element analysis (FEA) was performed to evaluate the residual bearing capacity of axially preloaded square hollow section (SHS) T-joints subjected to impact loading. First, the Bao–Wierzbicki fracture criterion was used to simulate the failure modes and behavior of specimens subjected to static axial compression and impacts, and the numerical results were compared with experimental results in the literature. The bearing capacity error between the numerical and experimental results was within 10%, which verified the accuracy of the finite element (FE) model. Then, the local and global displacements of joints were distinguished with the central line displacement method, and 40 FE models were created. The dynamic responses of joints under impact loading were used to study the resistance mechanism. Joint deformation mainly manifested as outward buckling of the chord webs and indentation of the chord upper flange. The in-plane restraint and support by the brace of the chord increased with the brace–chord width ratio. Finally, the ultimate residual bearing capacity coefficient ψ was defined as the ratio of the ultimate bearing capacities of the impacted and reference specimen, and the influence of different parameters, including axial preloading, impact energy, brace–chord width ratio, and chord diameter, was explored. Axial preloading and impact energy showed a negative correlation with ψ, while the brace–chord width ratio and chord diameter showed a significant positive correlation with ψ .